Bidirectional Modification of Buried Interface Reduces Energy Loss for Planar Perovskite Solar Cells with Efficiency >23%. Issue 5 (4th January 2023) - Sun, Weiwei; Wang, Kexiang; Liu, Weifeng; Huo, Xiaonan; Yin, Ran; Sun, Yansheng; Gao, Yukun; You, Tingting; Yin, Penggang
Abstract : Planar n–i–p perovskite solar cells (PSCs) based on a SnO2 electron transport layer dominate the certified high‐efficiency devices. However, the defects located at the SnO2 /perovskite interface (i.e., buried interface) or inside the perovskite films impede the further improvement of power conversion efficiency (PCE). Herein, nickel acetate (NiAc2 ) is introduced on buried interface as a bidirectional modifier to improve electron extraction of SnO2 and the crystal growth of perovskite for the first time. First, NiAc2 is chemically anchored on SnO2 to passivate oxygen vacancies, increase conductivity, and optimize the energy level alignment of the buried interface. Second, the porous morphology of PbI2 film deposited on NiAc2 ‐modified SnO2 endows more sufficient permeation and reaction of organic amine salts (formamidinium iodide [FAI] and methylammonium iodide [MAI]), forming high‐quality perovskite film with reduced PbI2 residues. Meanwhile, NiI2 and MAAc/FAAc may be produced via in situ reaction between NiAc2 and organic amine salts, which serve as interface modifier and crystallization regulator to further reduce defects located at the buried interface or inside the perovskite film, respectively. Consequently, an improved PCE of 23.02% for SnO2 ‐based PSCs with an ultrahigh open‐circuit voltage of 1.17 V is obtained. In addition, long‐term storage and light stability of the optimized PSCs are improved. Abstract : Nickel acetate (NiAc2 ) is introduced into SnO2 /perovskite interface as a bidirectional modifier to passivate oxygen vacancies of SnO2, optimize the energy level alignment of SnO2 /perovskite interface, as well as improve the crystal quality of perovskite, which significantly boost the power conversion efficiency of planar SnO2 ‐based perovskite solar cells to 23.02% with an ultrahigh open‐circuit voltage of 1.17 V.